Emotional and ideological construction in Husseini Elegies: A critical discourse analysis - Qasim Abbas Dhayef; Noura Khalid Al-Fatlawi (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2026)
This paper explores how exaggerated discourse is used to construct emotional intensity and ideological meaning in Hussaini elegies. Five extracts of elegies are analyzed in the paper based on the Critical Discourse Analysis, in particular the models of Norman Fairclough and Teun A. van Dijk, along with the theory of Appraisal. The results indicate that emotional expression is realised in a systematic way via somatic imagery, hyperbole, and cosmological metaphors, in which grief is embodied and universal instead of individual. The writings produce a polarized discursive level of morals, which implicitly sacrify martyrdom and declaim wrongdoing. The strategies of these languages work on the social practice level of ritual mourning to develop a sense of collective identity and recreate communal memory. The paper argues that exaggerated discourse is an ideological process which transforms previous trauma into intergenerational emotional heritage and it is by this process that cultural and religious meaning of Karbala is perpetuated.